Muslim History and Social Theory - Jung, Dietrich. author. aut Link
VIII, 133 p.
Keywords: This book combines contemporary discussions on modernity with the history of the Muslim world. From a heuristic perspective, it is sketching out a framework for a global sociology of modernity. This framework attempts to accommodate a core assumption of classical modernization theory – the global nature of modernity – with the pluralistic perspective of the rise of a multiplicity of historically concrete forms of modernities. It tries to reconcile a universalistic concept of modernity with the fact of modernity’s multiple historical realizations. At the same time, this discussion of contemporary social theory puts forward a critique of the still so conveniently applied equation of modernization with Westernization. In empirical terms, the book substantiates this critique in drawing its exemplary illustrations from the historical experience of Muslim peoples. Bringing Muslim history and discussions in social theory together, this book represents a synthesis of research efforts in sociology and Islamic studies.